Vibrio sp. dhg as a platform for the biorefinery of brown macroalgae - Hyun Gyu Lim (Nature Portfolio, 2019)
Brown macroalgae is a good candidate feedstock for biorefinery, but the major carbohydrate alginate cannot be digested by current industrial microbes. Here, the authors isolate Vibrio sp. dhg and engineer it to produce value-added biochemicals from alginate using newly developed genetic tools.